PHYSICAL PROPERTIES OF SWEET POTATO (NATIVE GISTING TANGGAMUS AND JATI AGUNG LAMPUNG SELATAN ON TWO STORAGE METHOD - Anisa Narullita; Sri Waluyo; Dwi Dian Novita (The University of Lampung, 2013)
The objective of this research was to observe the physical properties of two native of sweet potatoes (Ipomoea batatas) stored at two different conditions: temperature of 30 -32 °C with RH 58 – 70 % and temperature of 25 – 26 °C with RH 80 - 95 %. The two native of sweet potatoes used as sample were Gisting, harvested at 6 - 7 months, and Marga, harvested at 3 - 4 months. Parameters measured periodically during 8-week storage are weight loss, water content, number and length of prune, and the total soluble solid. The results showed that the storage temperature and RH are relatively stable during observation. During storage at temperature of 25 - 26 oC and RH 85 – 90 %, the weight loss was minimized and the total soluble solid increated sligtly for both native sweet potatoes. The decreasing water content during storage is not significantly different between Gisting and Marga. The increasing in number and length of prune was followed by the gain of weight loss. Gisting has longer storage time compared to Marga based on the standard of weight loss. Keywords:Sweet potato, physical properties, temperature, RH